2001
DOI: 10.1016/s0950-4230(01)00050-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of limits for effective flame acceleration in hydrogen mixtures

Abstract: Results of experimental data analysis on turbulent flame propagation in obstructed channels is presented. The data cover a wide range of mixtures: H 2 /air and H2/air/steam mixtures (from lean to rich) at normal and elevated initial temperatures (from 298 to 650K) and pressures (from 1 to 3 bars); and stoichiometric H 2 /02 mixtures diluted with N2, Ar, He, and C02 at normal initial conditions. The data set chosen covers, also, a wide range of scales exceeding two orders of magnitude. It is shown that basic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 16 publications
2
42
0
3
Order By: Relevance
“…13), the cell size 25 at Á D 0:75 is 21 mm, so that the decrease in the experimental impulse data at low equivalence ratios can not be explained by cell size effects. Following the work of Dorofeev et al, 28 the magnitude of the expansion ratio was examined for these mixtures. However, calculations for lean hydrogen-air showed that the expansion ratio is always higher than the critical value de ned 28 for hydrogen mixtures.…”
Section: Comparisons With Multicycle Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…13), the cell size 25 at Á D 0:75 is 21 mm, so that the decrease in the experimental impulse data at low equivalence ratios can not be explained by cell size effects. Following the work of Dorofeev et al, 28 the magnitude of the expansion ratio was examined for these mixtures. However, calculations for lean hydrogen-air showed that the expansion ratio is always higher than the critical value de ned 28 for hydrogen mixtures.…”
Section: Comparisons With Multicycle Experimentsmentioning
confidence: 99%
“…Following the work of Dorofeev et al, 28 the magnitude of the expansion ratio was examined for these mixtures. However, calculations for lean hydrogen-air showed that the expansion ratio is always higher than the critical value de ned 28 for hydrogen mixtures. Instead, the results may be explained by the transition distance of the mixtures.…”
Section: Comparisons With Multicycle Experimentsmentioning
confidence: 99%
“…Channels with obstacles are often used to study the flame acceleration and DDT in a controlled manner [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Considerable effort has been devoted to identifying the range of phenomenological behaviour of such flames and to deciphering the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations were followed by many years of theoretical code development, such as GASFLOW [48], DET-3D [49], and COM3D [50] and experimental investigations, such as the RUT experiments in Russia [51][52][53][54][55]. The conclusion can be drawn from these theoretical and experimental efforts that a large-volume hydrogen detonation following a core meltdown accident can be managed by the reactor containment of existing modern PWRs, like the Konvoi-PWRs of Kraftwerk Union [56].…”
Section: Hydrogen Detonationmentioning
confidence: 99%